Transcription of Cell Wall Mannoproteins-1 gene in Saccharomyces cerevisiae Mutant - Hermansyah Hermansyah (Syarif Hidayatullah State Islamic University, 2018)
Protein phosphatase (PPases) are enzymes to catalyze the phosphate groups removal from amino acid residues of proteins by protein kinases. The PPG1, one of PPases in Saccharomyces cerevisiae has less information in function/role. In this research, the disruption of DPPG1::CgHIS3 in FY833 genetic background was successfully constructed by PCR-mediated disruption strategies using pCgHIS3 (EcoRI-HindIII) (=pYMS314) (pUC19 base) and primer pair of PPG1, forward (41 to 100) and reverse (1048 to 1101). A BamHI - BamHI fragment 3,28 kb DPPG1::CgHIS3 consisting of 1 kb upstream PPG1+ 1.78 kb CgHIS3 + 0.5 down stream of PPG1) was confirmed using PCR and detected using electrophoresis. Phenotypic assay of DPPG1::CgHIS3 in FY833 and did not show 200mg/ml Calco fluor sensitivity, while another mutant DPPG1::CgHIS3 in W303-IA show 100mg/ml congo red sensitivity. Furthermore, to confirm whether DPPG1 could increase a CWP1 transcriptional level was performed Real Time (RT) PCR analysis using Primer pair Kf (AATTCGGCCTGGTGAGTATCC) and Kr (GTTTCAAAGTGCCGTTATCACT GT). RT-PCR’s data showed that transcriptional level of CWP1 in DPPG1::CgHIS3 changed less than two-folds comparing with in wild type strain. This result indicated that disruption of PPG1 in S.cerevisiae did not change CWP1 transcriptional level significantly.